Sistem Monitoring dan Kontrol Penjernih Greywater Bertenaga Photovoltaic Berbasis Internet of Things (IoT) - Hanifah Nur Kumala Ningrum; Raden Jasa Kusumo Haryo; Ryan Wicaksono; Yudhi Rizstu Nurcahyanto; Kaisar Bintang Putra (Nucleus Journal, 2025)
Water pollution due to human activities causes high levels of household wastewater called greywater. To reduce the impact of water pollution from greywater, wastewater needs to be processed to be safer for the environment. By utilizing technology and independent energy sources from Photovoltaics, a system was created that can purify wastewater and can be controlled and monitored using the Internet of Things. The research entitled "Monitoring and Control System for Photovoltaic Powered Greywater Purifiers Based on the Internet of Things (IoT)" aims to monitor and control water to obtain processed wastewater that produces cleaner water quality. This system can monitor battery charging for pump sources on filters in real time using IoT integrated with an Android application. The way this tool works is by utilizing the ESP8266 nodeMCU as a communication intermediary, Arduino as the tool control center, relays for control, voltage sensors to detect battery and pump voltage, ACS712 sensors to detect charging and pump currents, turbidity and pH sensors to detect water conditions. The results of this research are that the system can monitor water conditions, voltage, and pump current when filtering while controlling the pump based on water conditions, as well as monitoring the charging voltage and current from the PV to the battery.